Bowman‒Birk Inhibitor Suppresses Herpes Simplex Virus Type 2 Infection of Human Cervical Epithelial Cells - Yu Liu; Xi-Qiu Xu; Biao Zhang; Jun Gu; Feng-Zhen Meng; Hang Liu; Li Zhou; Xu Wang; Wei Hou; Wen-Zhe Ho (Viruses, 2018)
The Bowman‒Birk inhibitor (BBI), a protease inhibitor derived from soybeans, has been extensively studied in anti-tumor and anti-inflammation research. We recently reported that BBI has an anti-HIV-1 property in primary human macrophages. Because HSV-2 infection plays a role in facilitating HIV-1 sexual transmission, we thus examined whether BBI has the ability to inhibit HSV-2 infection. We demonstrated that BBI could potently inhibit HSV-2 replication in human cervical epithelial cells (End1/E6E7). This BBI-mediated HSV-2 inhibition was partially through blocking HSV-2-mediated activation of NF-κB and p38 MAPK pathways. In addition, BBI could activate the JAK/STAT pathway and enhance the expression of several antiviral interferon-stimulated genes (ISGs). Furthermore, BBI treatment of End1/E6E7 cells upregulated the expression of tight junction proteins and reduced HSV-2-mediated cellular ubiquitinated proteins’ degradation through suppressing the ubiquitin‒proteasome system. These observations indicate that BBI may have therapeutic potential for the prevention and treatment of HSV-2 infections.